مطالعہ کتب سے مشکلات کا حل: مشائخ کی آرا کا تحقیقی جائزہ: Problem Solving through Reading Books: An Appraisal of Mystical Approach - Dr. Allah Ditta; Dr. Maqbool Hasan Gillani; Aamir Waheed (International Research Journal of Arabic and Islamic Studies, 2023)
This article focuses to discuss the consecrations and sanctifications of reading books of some specific Islamic scholars. These books belong to renown Sufis of his time. These books belong to different branches of Islamic sciences especially Sufism. Sufis claim that reading these books will be a source or a method to accomplish and achieve their desires and wishes or to eliminate their complications and snags. Moreover, the disciples and followers of these saints would not only be benefitted with the pleasure of Allah Almighty but also, they would acquire the necessary knowledge about Islamic sciences as well. Sufis also, on the insistence and inquiry of her relatives and friends, has suggested some deeds and wazaif that any person can overcome their difficulties due to them. One of these, has been the study of books. Sufis told them that, not only good blessings will descend in this house and on this person, but difficulties will be removed and desires and needs are fulfilled. This paper has discussed the authenticity and validity of this method according to Quran and Sunnah and opinions of different scholars and jurists has also been elaborated as well. This article will enhance the appetite and carving about reading books in this era of Digitalization.